Femmes et activités physiques sous le régime de Vichy : politiques et enjeux médicaux - Fatia Terfous (Genre & Histoire)
This paper examines the political and medical ideas of women’s sport and physical education during the Second World War in France. The study uses national and private archives to show how, although women’s sport was not a priority either for politicians or doctors under the Vichy regime, they nonetheless raised the participation of French women in physical and sporting activities into a patriotic imperative. Sport and maternity were conceived of in close association in a perspective focused on the survival of the race. After having examined political and medical conceptions of women’s sport and physical education, this paper concludes with the question of how medical power participated in the institutionalization of women’s sport and what effects it had on the development of sports policy.